Endophytes – untapped resources and pharmacological prospects against coronaviruses - Erhirhie, Earnest Oghenesuvwe; Ezeagha, Chigozie Celestina; Okafor, Glory Chiamaka; Ikegbune, Chidozie; Mohammad, Mukim (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Viral infections stand to be among the most devastating diseases globally. Though significant efforts have been made in research and drug development against viral infections, the search for safe, affordable and effective vaccines against the current ravaging severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is still on. This is because already approved vaccines still need improvement. This review draws the attention of researchers on the potentials of bioactive substances from endophytes against the novel coronaviruses. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This assessment was made using references of articles published in English peer reviewed journals indexed in PubMed and Google Scholars databases up to June, 2022. The following key words were used; ‘coronaviruses’, ‘Endophytes’, ‘Endophytes and viral infections, ‘Endophytes and COVID-19, ‘SARS-CoV’. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. In-silico, in-vitro and in-vivo studies revealed that natural compounds from endophytes showed antiviral activities against various human coronavirus, including HCoV 229E and a norovirus surrogate, the feline coronavirus FCV F9, COVID-19, Coronavirus 2 (SARS-CoV-2), SARSCoV-2 Mpro, among others. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. This finding calls for researchers to also focus on endophytes, as part of drugs development in the bid to finding possible solution in combating the devastating COVID-19, an emerging situation.